(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2025)
This article analyzes the pedagogical conditions for developing students’ creative abilities in the process of their professional training. In the modern educational process, creative thinking and innovative approaches play a significant role, and the need to direct students toward independent thinking, problem-solving, and the formation of new perspectives is increasingly growing. The article examines the key pedagogical factors, methods, and technologies that influence the development of creative abilities and proposes effective approaches.